2012
DOI: 10.1136/bmj.e5660
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to diagnostic radiation and risk of breast cancer among carriers of BRCA1/2 mutations: retrospective cohort study (GENE-RAD-RISK)

Abstract: Objective To estimate the risk of breast cancer associated with diagnostic radiation in carriers of BRCA1/2 mutations. Design Retrospective cohort study (GENE-RAD-RISK).Setting Three nationwide studies (GENEPSO, EMBRACE, HEBON) in France, United Kingdom, and the Netherlands, Participants 1993 female carriers of BRCA1/2 mutations recruited in 2006-09.Main outcome measure Risk of breast cancer estimated with a weighted Cox proportional hazards model with a time dependent individually estimated cumulative breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
131
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(140 citation statements)
references
References 30 publications
4
131
4
1
Order By: Relevance
“…In the analysis of cancer risk in children from 160 families irradiated in Israel after World War II for an epidemic of tinea capitis, it was found that the increased meningioma incidence in irradiated children was determined by a subgroup of only 17 families (11%), where 4 of 5 children developed meningioma. 105 In addition, the large European cohort study GENE-RAD-RISK 106 has recently concluded that in carriers of BRCA1/2 mutations, any exposure to diagnostic radiation before the age of 30 years is associated with an increased risk of breast cancer. The relative risk in the mutant carrier was 1.9 and increased with dose.…”
Section: Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis of cancer risk in children from 160 families irradiated in Israel after World War II for an epidemic of tinea capitis, it was found that the increased meningioma incidence in irradiated children was determined by a subgroup of only 17 families (11%), where 4 of 5 children developed meningioma. 105 In addition, the large European cohort study GENE-RAD-RISK 106 has recently concluded that in carriers of BRCA1/2 mutations, any exposure to diagnostic radiation before the age of 30 years is associated with an increased risk of breast cancer. The relative risk in the mutant carrier was 1.9 and increased with dose.…”
Section: Carcinogenesismentioning
confidence: 99%
“…The relative risk in the mutant carrier was 1.9 and increased with dose. 106 Genetic predisposition may also drive the risk from exposure to charged particles. This is a critical issue for paediatric patients, a group that is often referred to proton therapy because much normal tissue can be spared compared with X-rays and, therefore, toxicity is reduced.…”
Section: Carcinogenesismentioning
confidence: 99%
“…For low-risk premenopausal women, alternative tests without radiation exposure (eg, ECG) or a no-testing strategy should be strongly considered. 40 Table 3 details the typical effective radiation dose for MPI, angiography, and CCTA. 35,41 Average background radiation exposure per year for a member of the US population is ≈3.1 mSv.…”
Section: Diagnostic Procedures For Ihd That Expose Women To Ionizingmentioning
confidence: 99%
“…This does not account for higher background risks of breast cancer or increased radiosensitivity suggested for BRCA1/BRCA2 carriers whose genetic defects give rise to impairment in DNA repair by homologous recombination, once the cell has lost both functioning copies of the gene. 15 However, it still remains to be shown that the cells which are heterozygous for a mutation are more radiosensitive. The current study is not powered to assess any effects in BRCA1/2 mutation carriers specifically, and as these females qualify for the more sensitive MRI screening, they may not need mammography.…”
mentioning
confidence: 99%
“…Nevertheless, we would not advocate commencing mammography ,30, in line with current UK recommendations. 15 The lower sensitivity of mammography in younger females 16 should be taken into account in determining its potential risks and benefits in these females. There was also no evidence of a greater carcinogenic effect of radiation in those estimated at particularly high breast cancer risk (.30%).…”
mentioning
confidence: 99%